Dihydroflavonol and Flavonol Derivatives from Macaranga recurvata - Mulyadi Tanjung (Natural product communications, 2012)
Two new dihydroflavonol derivatives, macarecurvatins A and B, have been isolated from the leaves of Macaranga recurvata (Euphorbiaceaae), along with the known compounds diisoprenylaromadendrin, glyasperin A and broussoflavonol F. The structures of the new compounds were determined on the basis of of 0.83 M. spectroscopic evidence. Upon cytotoxic evaluation against P-388 cells, macarecurvatin B showed strong activity with an IC 50